Rigid Esophagoscopy for an Impacted Kaffir Lime in the Proximal Esophagus: A Case Report and Discussion of a Unique Mechanical-Chemical Injury - Rita Risandi; Ade Asyari (HM Publisher, 2025)
Background: Esophageal food bolus impaction is a common otolaryngological emergency. However, impaction by a large, whole citrus fruit is exceedingly rare and presents unique diagnostic and therapeutic challenges, particularly concerning the object's size, radiolucency, and potential for causing both mechanical and chemical mucosal injury. Case presentation: We present the case of a 42-year-old male with acute-onset dysphagia and hypersalivation after ingesting a whole kaffir lime. Laryngoscopy revealed pooled secretions in the pyriform sinus, a key indicator of high esophageal obstruction, despite non-contributory plain radiography. The patient underwent emergent rigid esophagoscopy under general anesthesia. A 36 mm kaffir lime was identified at 15 cm from the incisors and successfully extracted en bloc using alligator grasping forceps. Post-extraction evaluation revealed localized mucosal excoriation without evidence of deep laceration or perforation. The patient recovered fully with no long-term sequelae. Conclusion: This case highlights the successful management of a rare and challenging esophageal foreign body. It underscores the diagnostic primacy of clinical findings over negative radiography for radiolucent objects and demonstrates the distinct advantages of rigid esophagoscopy—superior airway control, a wider operating channel, and use of robust instrumentation—for large, solid foreign bodies lodged in the proximal esophagus. In this instance, the impaction did not lead to severe complications within 24 hours, but prompt removal is essential to mitigate the risks of pressure necrosis and chemical esophagitis.